Plasmodium schizogony, a chronology of the parasite’s cell cycle in the blood stage - Voss, Yannik; Klaus, Severina; Guizetti, Julien; Ganter, Markus (PLoS pathogens, 2023)
Malaria remains a significant threat to global health, and despite concerted efforts to curb the disease, malaria-related morbidity and mortality increased in recent years. Malaria is caused by unicellular eukaryotes of the genus Plasmodium, and all clinical manifestations occur during asexual proliferation of the parasite inside host erythrocytes. In the blood stage, Plasmodium proliferates through an unusual cell cycle mode called schizogony. Contrary to most studied eukaryotes, which divide by binary fission, the parasite undergoes several rounds of DNA replication and nuclear division that are not directly followed by cytokinesis, resulting in multinucleated cells. Moreover, despite sharing a common cytoplasm, these nuclei multiply asynchronously. Schizogony challenges our current models of cell cycle regulation and, at the same time, offers targets for therapeutic interventions. Over the recent years, the adaptation of advanced molecular and cell biological techniques have given us deeper insight how DNA replication, nuclear division, and cytokinesis are coordinated. Here, we review our current understanding of the chronological events that characterize the unusual cell division cycle of P. falciparum in the clinically relevant blood stage of infection.